Pengaruh Model Pembelajaran Picture and Picture terhadap Kemampuan Berpikir Kritis Sejarah Siswa - Zhera Junius Mantira; Syaiful M; Suparman Arif (FKIP UNIVERSITAS LAMPUNG, 2017)
The purpose of this study is to determine whether There is positive and significant effect of Picture and Picture learning model of the ability in students' critical thinking history ability in the aspect of history courses at XI grade of Social Science class of SMAN 16 Bandar Lampung Academic Year 2015/2016. This study used Posttest-Only Control Group Design. The population in this study were students of XI grade Social Science class of SMAN 16 Bandar Lampung Academic Year 2015/2016. The sample was choosen randomly by using simple random sampling technique. Data analysis techniques in this research was the analysis of quantitative data with test data analysis with formula Eta and Test F, it can be concluded that there is positive effect with effect value is 0,49 and significant effeect is 18,32 by the effect of picture and picture learning model of students critical thinking ability.Tujuan penelitian ini untuk mengetahui